Metodología para el desarrollo de la motricidad gruesa en niños de 10 años. - Medrano Sánchez, Viky Lucila (2025)
This study focuses on the design and implementation of a methodology for developing gross motor skills in 10-year-old students at the "Catorce de Junio" Elementary School in Vinces. Using a mixed-method approach and a quasi-experimental design, the study identifies the main motor difficulties faced by students and evaluates current teaching practices. The results reveal the importance of integrating recreational and motor strategies adapted to the local context, demonstrating significant improvements in skills such as balance, coordination, and strength. This research highlights the need to prioritize practical physical education in the school curriculum to ensure children's comprehensive development.